Cabildos infantiles como espacios educativos durante el estallido social 2019 en Chile: una mirada desde la educación parvularia - Olivares Ramos, Marwill Milixa María (2023)
This research had as a general objective to understand and describe the pedagogical practices presented in the children’s councils erected in three communes of the Metropolitan Region, during the social explosion that occurred in Chile in 2019. It is a comprehensive, qualitative research with a study case research design, constituted by the views of three infant educators in training belonging to the University of Chile. The research was framed in the different perceptions that have regarding childhoods and how this has progressed over time thanks to legal decrees in addition to the levels of participation that could reach in these spaces. Through discourse analysis, it was possible to demonstrate the ability of children to understand events that adults often believe are not possible, Finally, it was possible to contrast the pedagogical practices presented in the children’s councils with what the curriculum of initial education in Chile proposes. It should be noted that, although it is a phenomenon that happened at a sociological level in the country, this inquiry emphasized the pedagogical and educational perspective that these spaces had. In view of the fact that the participants were early childhood children, is that the theme is linked to early childhood education and stresses the curriculum of formal preschool education